Analisis Kondisi Mengetahui Tentang Pengetahuan dan Implementasinya pada Pendidikan Abad 21 - Juniantari, Made; Setyosari, Punaji; Wedi, Agus; Utami, Wikan Budi (Jurnal Filsafat Indonesia, 2023)
Knowing is the most specific thought process and knowledge is the result. The branch of philosophy that examines the nature and theory of knowledge is called epistemology. The condition of knowing about knowledge needs to be analyzed so that it can be the basis for someone claiming a proposition as knowledge. A realistic question for the 21st century is what knowledge is most important for students and teachers to develop 21st century skills. The research method used is library research. The research was conducted by analyzing books, scientific articles, and relevant references related to the philosophy of knowledge and education in the 21st century. The results of the analysis provide information and meaning regarding the condition of knowing about knowledge and its implementation in the 21st century, including: 1) the variety of knowing consists of knowing that ( propositional knowledge), knowing how (practical/tacit knowledge), knowing will (aquitance), and knowing why; 2) proportional knowledge is formed based on the Justified True Belief (JTB) Condition formula; 3) data and information are two important and fundamental things in forming knowledge; and 4) there are three main categories of knowledge as the basis for 21st century learning, namely foundational knowledge (to know), meta knowledge (to act), and humanistic knowledge (to value).